Hypertension impairs myocardin function: a novel mechanism facilitating arterial remodelling - Pfisterer, Larissa; Feldner, Anja; Hecker, Markus; Korff, Thomas (Cardiovascular research, 2012)
AbstractAims. Hypertension evokes detrimental changes in the arterial vessel wall that facilitate stiffening and thus lead to a further rise in mean blood pres
Online publish-ahead-of-print 26 July
Gesehen am 21.11.2018